Generation of Reliable Red Cell Concentrate Requirement Lists for Operations and Interventions from Data Warehouse Data and Patient-Related Batch Documentation of Blood Components - Zimmermann, Robert; Becker, Andreas; Hackstein, Holger; Ganslandt, Thomas (Transfusionsmedizin, 2021)
Failure to perform transfusion-preparatory diagnostics and to order a sufficient number of blood components prior to surgery is increasingly leading to clinical emergencies and avoidable risks for patients. The mandatory preparation of blood requirement lists often fails due to the availability of suitable data. The University Hospital Erlangen is a tertiary care hospital with 1400 beds. Since 2010, all relevant data for the interpretation of patterns in the use of blood components have been continuously collected here. We are able to integrate the clinical data warehouse components of the personal data of red blood cell (RBC) recipients, the codes of inpatients in the German Diagnosis Related Group (G-DRG) system, ICD codes, OPS codes and the data of the RBC components from the blood bank's IT system. The obtained DRGs, ICD codes and OPS codes are linked to the data of blood component consumption on an individual basis. Analyses can be carried out for the entire hospital as well as for specific departments. Ongoing refinement of the database queries improves the ability to correctly estimate blood requirements for standard surgery and interventions. The results differ considerably from the surgeons' estimates of the probability of a transfusion, i.e. the probability of a transfusion is often underestimated. Correct compliance with the 10 percent transfusion probability limit for the question of early preoperative provision of cross blood can be improved by such queries. Counteracting the phenomenon of "delayed transfusion" is becoming an increasingly important task for the clinically active transfusion medicine specialist. Creating statistics on the probability of transfusion by linking data warehouse data and batch documentation data from blood banks can provide the necessary tools.
CRIS-Team WoS Importer:2021-03-26